Scanning Nanowire Probe Interferometer for Scalable Humidity Mapping. Issue 4 (24th February 2020) - Kim, Namho; Lee, Junho; Yong, Moon‐Jung; Yang, Un; Kim, Ji Tae; Kim, Jonghwan; Weon, Byung Mook; Kim, Chong Cook; Je, Jung Ho
Abstract: Quantifying humidity has long been an unavoidable task in science, industry, and society. Recent developments of nanoscience and technology that deal with ultrasmall droplets have aroused interest in microscopic moisture. Utilization of nanomaterials has been emerging as a promising strategy to miniaturize hygrometers for high‐sensitive, ultrasmall‐area sensing. However, a lack of high‐precision, on‐demand position control of sensing nanomaterials makes it difficult to explore spatial distribution of humidity at the micro‐ and nanoscale. Here, a scanning probe hygrometry (SPH) is developed that enables not only micro/nanoresolution but also scalable spatial mapping of humidity distribution. The SPH is realized with an unprecedented scanning nanowire probe interferometer (NPI) that is produced by direct 3D nanoprinting of a moisture‐sensitive polymer on a tapered optical fiber. Notably, the interferometric response of the NPI probe in ultrasmall areas quantitatively depends on humidity, arising from its refractive index change and volumetric swelling. By scanning the NPI probe and reading out the interferometric signals, multiscale spatial mapping of humidity distribution with versatile scanning steps from ≈10 2 nm to a few mm is demonstrated. The NPI is expected to provide a new nanoscale metrology that can answer fundamental questions about evaporation‐related science and engineering. Abstract : Scanning nanowire probe interferometer (NPI) for scalable humidity mapping is realized by developing a 3D nanoprinting of a moisture‐sensitive polymer nanowire. Humidity is measured by the NPI's moisture‐dependent interferometric response due to refractive index change and volumetric swelling. By scanning the NPI probe along x ‐ and z ‐axes, spatial mapping of relative humidity (RH) near a microwell has been successfully demonstrated.